To the problem of modeling of the country’s tourism image in the media - Jiamei, Song (Journal of the Belarusian State University. Journalism, 2019)
The article is devoted to the factors that have an influence on the development of the tourism industry and country’s image in the media environment. Different approaches to the factors classification and characteristics of the tourism image are investigated. The article also provides various Tut.by portal messages where China is perceived as a tourist destination and analyses linguistic means of Tut.by to create China’s tourist image. The work determines the factors that create China’s tourist image on the main Belarus web portal. The mass media role is represented as the one that stimulates the development of the tourism industry. The article examines the strategy of tourist image creation in modern mass media.
Keywords: tourist image; factors of optimization of tourist image; markers and means of language; mass media